ESSENTIAL ETAT: ONE-DAY PAEDIATRIC RESUSCITATION TRAINING IN A RESOURCE-LIMITED SETTING. Issue 10 (7th September 2013) - Dyer, B; Pollock, L; Morar, N; Clarke, E; Kampmann, B; Anderson, S
Abstract : Objectives & Background: WHO ETAT training courses provide comprehensive training in paediatric emergency care over 3.5–5 days and have been shown to improve outcome in resource-limited settings. However, the logistics, cost and impact on local service delivery of a five-day course may limit training opportunities in some settings. In this context, we aimed to determine whether a shorter, more focused course would be feasible. Methods: A one-day training course, 'Essential ETAT', was adapted from WHO ETAT training materials and included practical and lecture-based sessions on triage, cardiopulmonary resuscitation and recognition and management of key paediatric emergencies. Practical sessions in airway management, bag-valve-mask ventilation and intra-osseous needle insertion were included. A short manual summarizing ETAT guidelines was provided. Participants were all nurses or doctors working in primary or secondary care settings in The Gambia. The main outcome measure was participant knowledge, assessed by improvement in scores between pre and post-course multiple-choice tests. This was compared to similar data from a historical control group (n=76) who had completed standard 3.5 day ETAT training. Results: 57 participants completed the Essential ETAT one-day training course. Participants showed a significant improvement in post-course test scores; mean score pre-course 62.6% (95% CI 58.5–68.7%), post-course 78.4% (75.1–81.7%), p<0.0001. There was no significant difference in mean improvement in post-course test scores between Essential ETAT participants and the standard ETAT historical control (15.8% (12.1–19.5%) vs 14.7% (11.5–17.9%), p=0.67). Conclusion: 'Essential ETAT' was well received by participants and improvements in post-course test scores compared well to results from standard ETAT courses. Further evaluation is required to indicate whether knowledge is retained and changes clinical practice. Focused, short duration resuscitation training may offer a pragmatic and potentially cost-effective alternative to standard courses.